Rethinking Tax Sovereignty in a Globalized Economy: An Indonesian Perspective (Indonesian Tax Justice Review, 2024)
Globalization and international tax coordination have fundamentally reshaped national tax sovereignty. This paper examines Indonesia’s experience in navigating global tax initiatives and their implications for domestic policy autonomy. Using theoretical and doctrinal analysis, the study explores how international standards affect developing countries’ capacity to pursue equitable tax policies. The findings suggest that formal participation in global frameworks does not necessarily translate into substantive influence. This paper contributes to the global tax justice literature by proposing a reconceptualization of tax sovereignty as inclusive global participation rather than mere compliance. Indonesia’s case underscores the need for reforming international tax governance to reflect diverse development realities and promote equitable outcomes.